2010
DOI: 10.1002/cncr.25807
|View full text |Cite
|
Sign up to set email alerts
|

Novel approach using antimicrobial catheters to improve the management of central line‐associated bloodstream infections in cancer patients

Abstract: BACKGROUND: Central venous catheter (CVC) removal has often been recommended for the treatment of central line‐associated bloodstream infections (CLABSIs). However, CVC removal is not always practical in patients with cancer, and changing CVCs with noncoated CVCs over guidewire may result in cross‐infection of the new CVC. Therefore, the current matched retrospective cohort study was conducted to evaluate the effectiveness of exchanging infected CVCs for minocycline‐ and rifampin (MR)‐coated CVCs in cancer pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The results from the in vitro exchange model for M/R CVCs were consistent with those of a recent clinical study from our center showing that the exchange of culprit CVCs for new M/R CVCs in the setting of CLABSI was useful in improving the overall response rate, decreasing the risk of mechanical failure, and decreasing disease recurrence (27). Another clinical study from our group revealed that exchanging colonized CVCs over guide wires for M/R CVCs was an effective alternative to removing and inserting new CVCs at a new vascular site in the setting of S. aureus infection and CLABSI (28; A. M. Chaftari and A. El Zakhem, submitted for publication).…”
Section: Discussionsupporting
confidence: 87%
“…The results from the in vitro exchange model for M/R CVCs were consistent with those of a recent clinical study from our center showing that the exchange of culprit CVCs for new M/R CVCs in the setting of CLABSI was useful in improving the overall response rate, decreasing the risk of mechanical failure, and decreasing disease recurrence (27). Another clinical study from our group revealed that exchanging colonized CVCs over guide wires for M/R CVCs was an effective alternative to removing and inserting new CVCs at a new vascular site in the setting of S. aureus infection and CLABSI (28; A. M. Chaftari and A. El Zakhem, submitted for publication).…”
Section: Discussionsupporting
confidence: 87%
“…Recent clinical epidemiology studies have reported that the rates of immediate complications for catheter insertions range from 7.5% in hematology patients to 7.7% in general hospital patients when performed by a dedicated central venous catheter (CVC) placement service using ultrasound guidance or 29.4% without ultrasound guidance (3,4). The role of catheter exchange over a guidewire, which might be of benefit in some situations due to bacterial CRBSIs (5), is undefined in CR-BSIs caused by Candida (6).…”
mentioning
confidence: 99%
“…In addition, the authors of the letter propose another novel potential indication for the use of impregnated catheters; that is, in patients with documented CRBSI whose CVC must be removed, according the results of Chaftari and colleagues. 5,6 Those studies found a similar clinical response and relapse rate between patients who had a CVC exchanged over guidewire for minocycline/rifampincoated CVCs and patients in whom the CVC was removed. In addition, the in vitro catheter exchange model revealed that catheter exchange over guidewire using minocycline/rifampin-coated CVCs completely prevented biofilm colonization compared with exchange using uncoated CVCs.…”
Section: To the Editormentioning
confidence: 84%